AN ANALYSIS OF “IDA I DO AND OKE” TRADITIONAL SONG: A FORM OF HELONG LANGUAGE MAINTENANCE - Ifoni Ludji (Postgraduate School, Universitas Nusa Cendana, 2019)
Literary activities are not limited by particular activity of rituals. It covers almost cultural aspects and routines of certain socio-cultural community can be represented by activity of literature. To keep using traditional songs is a kind of literary activities along with local language and mother tongou maintenance. This kind of literary activity is very positive because it caries local language and local content like deletion, metathesis, reduplication, compound words, acronym, sentence patters, articles, meaning and metaphor. It also contains religious values, spirit, and social values.